Accuracy of contemporary oesophageal cancer lymph node staging with radiological-pathological correlation. Issue 8 (August 2017) - Foley, K.G.; Christian, A.; Fielding, P.; Lewis, W.G.; Roberts, S.A.
Abstract : Aim: To evaluate the accuracy of contemporary N-staging and provide radiological–pathological correlation in patients with lymph node metastases (LNMs) that were radiologically staged N0. Materials and methods: One hundred and twelve patients were included who underwent surgery alone ( n =41) or neoadjuvant therapy ( n =71) between October 2010 and December 2015. Contrast-enhanced computed tomography (CECT), endoscopic ultrasound (EUS), and combined positron-emission tomography (PET) and CT N-stage were compared to pathological N-stage [node-negative (N0) versus node-positive (N+) groups]. Fifty LNMs from 15 patients preoperatively staged as N0 were measured and the maximum size recorded. Results: Accuracy, sensitivity, and specificity of N0 versus N+ disease with CECT, EUS, and PET/CT was 54.5%, 39.7% and 77.3%, 55.4%, 42.6% and 75%, and 57.1% 35.3%, and 90.9%, respectively. All techniques were more likely to under-stage nodal disease; CECT (X 2 32.890, df=1, p <0.001), EUS (X 2 28.471, df=1, p <0.001), and PET/CT (X 2 50.790, df=1, p <0.001). PET/CT was more likely to under-stage nodal disease than EUS ( p =0.031). Median LNM size was 3 mm, with 41 (82%) of LNMs measuring <6 mm and 22 (44%) classified as micro-metastases (≤2 mm). Conclusion: This study has demonstrated poor N-staging accuracy in the modern era of radiological staging. Eighty-two percent of LNMs measured <6 mm, making direct identification extremely challenging on medical imaging. Future research should focus on investigating and developing alternative surrogate markers to predict the likelihood of LNMs. Highlights: CECT, EUS and PET/CT N-staging accuracy is poor in oesophageal cancer. CECT, EUS and PET/CT are all more likely to under-stage nodal disease. Many lymph node metastases are too small to be identified with direct imaging.